HUBUNGAN MINAT DAN PRESTASI BELAJAR MENJAHIT DENGAN KESIAPAN KERJA SISWA SMK - Arwita Priyani (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2016)
The purpose of this study is to analyzethe relationship of interest and learningachievement of sewing simultaneously andpartially with the readiness of student work inSMKN I Pogalan-Trenggalek. This research is acorrelational descriptive with quantitativeapproach. The population of this study is thestudents of Class XII of the Year 2012201/20/2016 Fashion Skill Program by usingproportional random sampling 60% and 10%reserve. The number of samples in this studywas 50 students. Data collection of interest andreadiness of work using questionnaires withLikert scale, while the data of learningachievement sewing using secondary data fromthe value of report cards. Data analysistechniques to test hypotheses 1 and 2 are partialcorrelations whereas hypothesis 3 uses multipleregression correlation techniques. The resultsshowed that simultaneously and partially therewas a positive and significant relationshipbetween interest and learning achievement ofsewing to the readiness of work